Tomographic follow-up of bone regeneration after bone block harvesting from the mandibular ramus - Diez, G. F.; Fontao, F. N. G. K.; Bassi, Ana Paula Farnezi [UNESP]; Gama, J. C.; Claudino, M. (Churchill Livingstone, 2014)
Autogenous bone is still considered the gold standard, and the applicability of autogenous bone grafts is well established. However, the possibility of second harvesting from the same donor region remains unclear. The aim of this study was to perform a prospective evaluation of hard tissue deposition in the mandibular ramus after bone block harvesting using cone beam computed tomography (CBCT). Twenty-two patients with indications for augmentation procedures using autogenous bone from the mandibular ramus were selected. Three CBCT scans were performed with a tomographic guide before bone harvesting (T1) and at 14 days (T2) and 6 months (T3) after the surgical procedures. Measurements were obtained in 2D (area, mm(2)) and 3D (volume, mm(3)), and were subsequently compared. In the 2D analysis, the mean bone formation rate was 56%, while for the 3D analysis the mean rate was 9.7%. Despite this difference, there was a significant correlation between area and volume measurements. Our findings demonstrated the presence of hard tissue in the mandibular ramus at 6 months after bone harvesting, which suggests that it would be possible to reuse the same region for a second block harvesting. However, the second bone harvesting would involve less bone for transplantation when compared to the first bone harvesting.
Keywords: bone transplantation; cone beam computed tomography; bone regeneration